2018
DOI: 10.1016/j.molcel.2018.01.019
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methyladenosine Guides mRNA Alternative Translation during Integrated Stress Response

Abstract: The integrated stress response (ISR) facilitates cellular adaptation to stress conditions via the common target eIF2α. During ISR, the selective translation of stress-related mRNAs often relies on alternative mechanisms, such as leaky scanning or reinitiation, but the underlying mechanism remains incompletely understood. Here we report that, in response to amino acid starvation, the reinitiation of ATF4 is not only governed by the eIF2α signaling pathway, but is also subjected to regulation by mRNA methylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
214
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(231 citation statements)
references
References 58 publications
(87 reference statements)
16
214
1
Order By: Relevance
“…Recently, m 6 A modifications in the 5′ UTR of the ATF4 mRNA have been discovered. These modifications regulate ATF4 translation by stalling scanning ribosomes on uORF2, thereby reconfiguring translation in response to low ternary complex availability . Although this is a specific, highly characterized example of alternate uORF usage, it illustrates the general principle that uORF usage can change in response to physiological conditions.…”
Section: How Cellular Stress Affects Translationmentioning
confidence: 90%
“…Recently, m 6 A modifications in the 5′ UTR of the ATF4 mRNA have been discovered. These modifications regulate ATF4 translation by stalling scanning ribosomes on uORF2, thereby reconfiguring translation in response to low ternary complex availability . Although this is a specific, highly characterized example of alternate uORF usage, it illustrates the general principle that uORF usage can change in response to physiological conditions.…”
Section: How Cellular Stress Affects Translationmentioning
confidence: 90%
“…The RIOK3 and CIRBP 225 peaks span four and three DRACH motifs, respectively. Both peaks have been previously 226 reported in published datasets, although the function of m 6 A on these transcripts has not been 227 investigated; the RIOK3 peak was identified in mouse liver tissue (Zhou et al, 2018) MeRIP-RT-qPCR on RNA from cells infected with DENV, ZIKV, and HCV to validate these 230 predicted changes in m 6 A, as in Figure 1F. MeRIP-RT-qPCR confirmed that relative to gene 231 expression, the m 6 A modification of RIOK3 significantly increased following infection and that of 232 CIRBP decreased, while RIOK3 and CIRBP mRNA levels both increased following infection 233 ( Figure 1F Fredericksen, 2010; Suthar et al, 2013).…”
Section: Pathways 218mentioning
confidence: 92%
“…More recently, other modifications including the methylation of internal adenosine nucleotides to form N 6 -methyladenosine (m 6 A) have emerged as means to regulate mRNA functions such as protein synthesis in a variety of contexts, including in response to stress (Roundtree, Evans, Pan, & He, 2017;Zhou et al, 2018). In yeast, although m 6 A is widespread across different mRNAs, its presence is restricted to meiosis (sporulation), where m 6 A patterns vary over time (Schwartz et al, 2013).…”
Section: Mrna Modificationsmentioning
confidence: 99%